THE ROLE OF ATTACHMENT QUALITY, AGE AND GENDER TO PROSOCIAL BEHAVIOUR - Siti Marliah Tambunan (Jurnal Psikologi, 2007)
The aim of this study is to measuring the role of attachment quality, age and gender toprosocial behavior. Participants of this study are 204 children and adolescence in schoolage. The result shows significant role from attachment quality, age dan gender toprosocial behavior and also the difference of prosocial behavior based on attachmentquality, age and gender.Key words: prosocial behavior, attachment quality, age, gender